PhyFizball: a game-based tool to enhance student’s understanding of force and motion - Muhammad Alfi Yusra Jalani; Adibah Abu Bakar; Syazwan Saidin (Institute of Advanced Engineering and Science, 2026)
Difficulties in understanding the concepts of force and motion continue to challenge secondary school students due to the abstract nature of physics and the limited use of interactive teaching methods. This study introduces PhyFizball, a pinball-inspired, low-cost game-based learning (GBL) tool designed to make physics learning more engaging and concrete. The tool aims to help students visualize fundamental concepts such as Newton’s laws, friction, and the relationship between force and motion through hands-on and collaborative gameplay. A quasi-experimental pretest–posttest control group design was employed with 30 form two students from a Malaysian secondary school, divided equally into experimental (n =15) and control (n =15) groups. Over four weeks, the experimental group learned using PhyFizball, while the control group received conventional lecture-based instruction. A validated conceptual understanding test was administered before and after the intervention. Results from paired and independent t-tests revealed that the experimental group achieved significantly higher post-test scores than the control group (t(28) =3.282, p =0.003). The findings confirm that PhyFizball effectively enhances students’ conceptual understanding and engagement in learning physics. Its accessible design demonstrates potential as a cost-effective and scalable teaching tool for improving science learning outcomes in secondary education.